Morphometric Variations, Length and Weight of Snapper (Lutjanus malabaricus) Caught in the Waters of Saleh Bay, Sumbawa - sary, ratna; Bachri, Syamsul; Kautsari, Neri; Ahdiansyah, Yudi; Mardhia, Dwi (Fisheries Science Study Program, Faculty of Science and Technology, Muhammadiyah University of Sidenreng Rappang., 2025)
Red Snapper (Lutjanus malabaricus) belongs to the Lutjanidae family and is highly valued economically, making it one of the main commodities in the capture fisheries sector in Indonesia. Studies on morphometric variation and its relationship with length and weight are essential to support the sustainable management and conservation of fishery resources. This study was conducted to evaluate the morphometric variation and the length-weight relationship pattern of Red Snapper caught in the waters of Saleh Bay, Sumbawa, as part of efforts to understand its growth dynamics. A total of 15 Red Snapper specimens were obtained from fish collectors in Labuhan Terata, Labuhan Kuris Village, in November 2024. Twelve morphometric characteristics were measured to assess body size variability. Additionally, to determine the growth pattern, the relationship between length and weight was analyzed using regression equations. The study found that the total length of the fish ranged from 44–59 cm, while their weight varied between 1.365 and 2.294 g. Based on the length-weight relationship analysis, it was found that Red Snapper exhibited a positive allometric growth pattern, where body length increases more rapidly than weight. These findings provide basic information on the morphometric characteristics and growth dynamics of Red Snapper in the waters of Saleh Bay. This data can serve as a reference for sustainable fish stock management and assist in formulating science-based fisheries policies to maintain the conservation of Red Snapper populations in the area.